1998
DOI: 10.1007/s004110050124
|View full text |Cite
|
Sign up to set email alerts
|

Neutron, proton, and photonuclear cross-sections for radiation therapy and radiation protection

Abstract: Les Afamos Natlonsl Moratory, an affirmative astiedequal oppertun"kyempleyer, is operated by the Unheraiiy of CMomia for the U.S. Deparbnent of Ene&y under mntract W-740MNG-36. By accaptanca of this article, the publisher rewgnfzes that the U.S. Gwemment retafns a nonexslustie, reya~free license to pubfii or repreduce the pubfried form of thii scmtributien, or to allow others 10 do SO,for U.S. Government purposes. The k Afamos National Laberatmy requests that the pubfkher identify this article aa wxk perfonnad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 30 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…Such data permit calculations of absorbed dose in the body from therapy beams, and through use of kerma coefficients allow absorbed dose to be estimated for a given neutron energy distribution. Most work in the beginning was done by Chadwick ( 1 ) and was extended afterward by many other authors. Monte Carlo simulations of the neutron dose and neutron energy spectra were performed for typical proton therapy facilities.…”
Section: Introductionmentioning
confidence: 99%
“…Such data permit calculations of absorbed dose in the body from therapy beams, and through use of kerma coefficients allow absorbed dose to be estimated for a given neutron energy distribution. Most work in the beginning was done by Chadwick ( 1 ) and was extended afterward by many other authors. Monte Carlo simulations of the neutron dose and neutron energy spectra were performed for typical proton therapy facilities.…”
Section: Introductionmentioning
confidence: 99%
“…By applying Equation (9) and Equation (10) to the observed and computed data, the RMSE and NSE values for the three equations are calculated and given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Rutherford concluded that a nitrogen atom is composed of positively charged protons and negatively charged electrons, and that a nitrogen atom can be converted to oxygen and a proton (hydrogen atom nucleus) [14,15]. Following the discovery of the proton, James Chadwick at Lawrence Berkeley Laboratory discovered the neutron and studies subsequently began assessing potential applications of fast neutron radiation therapy [16][17][18].…”
Section: Proton Discoverymentioning
confidence: 99%